2014
DOI: 10.1016/j.hlc.2013.07.012
|View full text |Cite
|
Sign up to set email alerts
|

Long-term Clinical Outcomes of Statin Use for Chronic Heart Failure: A Meta-analysis of 15 Prospective Studies

Abstract: Based on the available data, statins persistently decreased all-cause mortality and the incidence of rehospitalisation for heart failure in CHF patients, and the benefits might be partially associated with use of specific statin.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
28
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(30 citation statements)
references
References 39 publications
0
28
0
1
Order By: Relevance
“…Atorvastatin treatment appeared to reduce all-cause mortality (RR ¼ 0.61, P ¼ .05) and rehospitalization for HF (RR ¼ 0.44, P ¼ .04) compared with nonatorvastatin therapy. 4 These effects were also seen in the GREek Atorvastatin and Coronary-heart-disease Evaluation (GREACE) study 5 and the large Treating to New Targets (TNT) study. 6 According to TNT, improvement in kidney function may be related to the beneficial effect of high-dose atorvastatin on HF hospitalizations.…”
mentioning
confidence: 88%
See 1 more Smart Citation
“…Atorvastatin treatment appeared to reduce all-cause mortality (RR ¼ 0.61, P ¼ .05) and rehospitalization for HF (RR ¼ 0.44, P ¼ .04) compared with nonatorvastatin therapy. 4 These effects were also seen in the GREek Atorvastatin and Coronary-heart-disease Evaluation (GREACE) study 5 and the large Treating to New Targets (TNT) study. 6 According to TNT, improvement in kidney function may be related to the beneficial effect of high-dose atorvastatin on HF hospitalizations.…”
mentioning
confidence: 88%
“…3 A few days ago, a meta-analysis of 15 prospective studies, involving 45 110 patients, addressed the issue of statin treatment for HF. 4 The study included patients with both preserved and reduced ejection fraction. Additional statin treatment was associated with reduced all-cause mortality (risk ratios [RRs] ¼ 0.71, 95% confidence intervals [CIs] 0.61-0.83) and reduced rehospitalization rate for HF (RR ¼ 0.84, 95% CI 0.74-0.96).…”
mentioning
confidence: 99%
“…Atorvastatin significantly reduced the rates of adverse outcomes including SCD in the highest quartile of LDL-C (≥145 mg/dl [>3.76 mmol/L]) in patients with DMt2 undergoing hemodialysis [28,29] . The most recent meta-analysis of 15 studies and 45 110 patients indicated that statins decreased all-cause mortality in CHF patients, but there was no statistically significant effect of statin therapy on reduction in the risk of sudden cardiac death in these patients [30] . Studies included in this meta-analysis evaluated simvastatin (n = 1), rosuvastatin (n = 2), atorvastatin (n = 3), multiple statins (n = 4) and non-specified statin treatment (n = 5).…”
Section: Statin Therapy and Scdmentioning
confidence: 99%
“…Studies included in this meta-analysis evaluated simvastatin (n = 1), rosuvastatin (n = 2), atorvastatin (n = 3), multiple statins (n = 4) and non-specified statin treatment (n = 5). Based on the subanalysis the authors suggested that some statins, such as atorvastatin (hydrophilic), might provide more beneficial effects in CHF patients [30] . The kind of statin chosen for the therapy might be an important factor influencing the efficacy in patients with CHF.…”
Section: Statin Therapy and Scdmentioning
confidence: 99%
“…A recent meta-analysis of 15 prospective studies (n=45,110) addressed the effects of statins in patients with HF [88]. The study included patients with both preserved and reduced EF and showed a reduction in all-cause mortality in patients treated with statins (risk ratio (RR) 0.71, 95% confidence interval (CI) 0.61-0.83) and a reduction in rehospitalization rate for HF (RR 0.84, 95% CI 0.74-0.96) [88].…”
Section: Emerging Treatmentsmentioning
confidence: 99%